Growth of turbot (Scophthalmus maximus L.) from 1 to 3,000 g in the north of Spain - Fernández-Pato, Carlos; Martínez-Tapia, Concha; Chereguini-Fernández-Maquieira; María del Olvido; Sola, Esperanza (2012)
Growth of Turbot from 1 y. to 3000 g. is related in this paper. Groups of fish were fed on semihumid food. Gompertz's and Bertalanffy's equations were applied for growth in weight and length respectively. Parameters such as food conversion index and specific growth rate, as well as condition factor were calculated.Growth is presented as a curve-line for different intervals. No